Effect of Solar Wind Pressure and Substorm Linked Particle Injection on Local Time Distribution of Electromagnetic Ion Cyclotron Waves - Upadhyay, Aditi; Kakad, Bharati; Kakad, Amar; Rawat, R. (Frontiers in Astronomy and Space Sciences, 2022)
Several observations of electromagnetic ion cyclotron (EMIC) waves have been reported from the Earth’s magnetosphere. It is an important component of space weather research due to its efficient role in precipitating highly energetic electrons from the Earth’s radiation belt. In general, the interplanetary solar wind conditions and geomagnetic activity control the generation of EMIC waves by modifying the ambient plasma conditions in the generation region. Therefore, EMIC wave occurrence patterns observed both in space and on the ground are influenced by the variations in the parameters like auroral electrojet (AE index), solar wind dynamic pressure, and Dst, which represent the magnetospheric conditions. We present a detailed local time distribution of EMIC waves observed at the Antarctic station, Maitri (geographic 70.7oS, 11.8oE, L = 5), for 2011–2017. We have cataloged the EMIC wave occurrence in four frequency ranges (between 0.12–2 Hz) and examined their occurrence pattern for different levels of AE index and solar wind pressure. The present analysis reveals that at the ground station, Maitri, the occurrence of EMIC waves is dominated in the lower frequency range (0.12–1 Hz) with lower occurrence in the higher frequency range (>1Hz). It is found that the EMIC waves having frequencies > 1 Hz occur dominantly in the early morning hours with a peak close to 5.7 LT hours, and they are linked to the magnetic activity that occurred in the preceding days, whereas the effect of solar wind dynamic pressure and AE index on the local time occurrence of EMIC waves is unambiguously seen for the waves with <1 Hz. The study revealed the larger AE index shifts occurrence of EMIC waves in the dusk sector.